Mathematical modeling & bloom’s taxonomy in the higher course of civil engineering - Rodrigues, Vitor Franco (Seven Editora, 2023)
Different techniques and didactic methodologies are used in the teaching of mathematics from the basic, secondary, and higher levels, constantly seeking to improve the results of teaching/learning and ensure the perpetuation of knowledge and the development of new knowledge and technologies. This article addresses in the format of a bibliographic review, the methodology of Mathematical Modeling (MM), compared and linked to the educational objectives of Bloom’s Taxonomy, pointing out within the MM the possible reaches of the cognitive and affective domains, having as main approach the teaching of Mathematics in the higher course of Civil Engineering. The result of the work presents a proposal of an active class script, with the methodology of MM, intended for Civil Engineering academics, in which at each stage of the class are highlighted the possible achievements of the cognitive and affective objectives of Bloom’s Taxonomy and, finally, the conclusion of the article highlights the importance of developing innovative methodologies in teaching, seeking the formation of ethical citizens and able to solve problems and who have autonomy, resilience, innovative critical sense, contributing to scientific knowledge and the advancement of the world. DOI:https://doi.org/10.56238/alookdevelopv1-115